Molecular detection of human bacterial pathogens - Liu, Dongyou (CRC Press, 2011)
"As more original molecular protocols and subsequent modifications are described in the literature, it has become difficult for those not directly involved in the development of these protocols to know which are most appropriate to adopt for accurate identification of bacterial pathogens. Molecular Detection of Human Bacterial Pathogens addresses this issue, with international scientists in respective bacterial pathogen research and diagnosis providing expert summaries on current diagnostic approaches for major human bacterial pathogens. Each chapter consists of a brief review on the classification, epidemiology, clinical features, and diagnosis of an important pathogenic bacterial genus, an outline of clinical sample collection and preparation procedures, a selection of representative stepwise molecular protocols, and a discussion on further research requirements relating to improved diagnosis. This book represents a reliable and convenient reference on molecular detection and identification of major human bacterial pathogens; an indispensable tool for upcoming and experienced medical, veterinary, and industrial laboratory scientists engaged in bacterial characterization; and an essential textbook for undergraduate and graduate students in microbiology"--Provided by publisher.